Jigsaw Puzzle Improve Fine Motor Abilities of Upper Extremities in Post-Stroke Ischemic Clients - Kusnanto Kusnanto; Eska Dwi Prajayanti; Harmayetty Harmayetty (Universitas Airlangga, 2017)
Introduction: Ischemic stroke is a disease caused by focal cerebral ischemia, where is a decline in blood flow that needed for neuronal metabolism, leading to neurologic deficit include motor deficit such as fine motor skills impairment. Therapy of fine motor skills disorders is to improve motor function, prevent contractures and complications. These study aimed to identify the effect of playing Jigsaw Puzzle on muscle strength, extensive motion, and upper extremity fine motor skills in patients with ischemic stroke at Dr. Moewardi Hospital, Surakarta.Methods: Experimental Quasi pre-posttest one group control. The number of samples were 34 respondents selected using purposive sampling technique. The samples were divided into intervention and control groups. The intervention group was 17 respondents who were given standard treatment hospital and played Jigsaw Puzzle 2 times a day for six days. Control group is one respondent given by hospital standard therapy without given additional Jigsaw Puzzle game. Evaluation of these research is done on the first and seventh day for those groups.Results: The results showed that muscle strength, the range of joint motion and fine motor skills of upper extremities increased (p = 0.001) significantly after being given the Jigsaw Puzzle games. These means playing Jigsaw Puzzle increase muscle strength, the range of joint motion and upper extremity fine motor skill of ischemic stroke patients.Conclusion: Jigsaw puzzle game administration as additional rehabilitation therapy in upper extremity fine motor to minimize the occurrence of contractures and motor disorders in patients with ischemic stroke. Jigsaw puzzle game therapy capable of creating repetitive motion as a key of neurological rehabilitation in Ischemic Stroke. This study recommends using jigsaw puzzle game as one of intervention in the nursing care of Ischemic Stroke patients.